Highly sensitive label-free bio-interfacial colorimetric sensor based on silk fibroin-gold nanocomposite for facile detection of chlorpyrifos pesticide - Mane, Pramod C.; Shinde, Manish D.; Varma, Sanjana; Chaudhari, Bhushan P.; Fatehmulla, Amanullah; Shahabuddin, M.; Amalnerkar, Dinesh P.; Aldhafiri, Abdullah M.; Chaudhari, Ravindra D. (Scientific Reports, 2020)
Herein, the preparation of gold nanoparticles-silk fibroin (SF-AuNPs) dispersion and its label-free colorimetric detection of the organophosphate pesticide, namely chlorpyrifos, at ppb level are reported. The silk fibroin solution was extracted from B. mori silk after performing degumming, dissolving and dialysis steps. This fibroin solution was used for synthesis of gold nanoparticles in-situ without using any external reducing and capping agent. X-ray Diffractometry (XRD), Field Emission Transmission Electron Microscopy (FETEM) along with Surface Plasmon Resonance based optical evaluation confirmed generation of gold nanoparticles within SF matrix. The resultant SF-AuNPs dispersion exhibited rapid and excellent colorimetric pesticide sensing response even at 10 ppb concentration. Effect of additional parameters viz. pH, ionic concentration and interference from other pesticide samples was also studied. Notably, SF-AuNPs dispersion exhibited selective colorimetric pesticide sensing response which can be calibrated. Furthermore, this method was extended to various simulated real life samples such as tap water, soil and agricultural products including plant residues to successfully detect the presence of chlorpyrifos pesticide. The proposed colorimetric sensor system is facile yet effective and can be employed by novice rural population and expert researchers alike. It can be exploited as preliminary tool for label-free colorimetric chlorpyrifos pesticide sensing in water and agricultural products.

Mechanistic insight into differential interactions of iron oxide nanoparticles with native, glycated albumin and their effect on erythrocytes parameters - Nisar, Akib; Ajabia, Devangi K.; Agrawal, Sanskruthi B.; Varma, Sanjana; Chaudhari, Bhushan P.; Tupe, Rashmi S. (International Journal of Biological Macromolecules, 2022)
Nanoparticles and protein bioconjugates have been studied for multiple biomedical applications. We sought to investigate the interaction and structural modifications of bovine serum albumin (BSA) with iron oxide nanoparticles (IONPs). The IONPs were green synthesized using E. crassipes aqueous leaf extract following characterization using transmission electron microscopy, energy dispersive X-ray analysis and X-ray diffraction. Two different concentrations of native/glycated albumin (0.5 and 1.5 mg/ml) with IONPs were allowed to interact for 1 h at 37 degrees C. Glycation markers, protein modification markers, cellular antioxidant, and hemolysis studies showed structural modifications and conformational changes in albumin due to the presence of IONPs. UV-visible absorbance resulted in hyperchromic and bathochromic effects of IONPs-BSA conjugates. Fluorescence measurements of tyrosine, tryptophan, advanced glycated end products, and ANS binding assay were promising and quenching effects proved IONPs-BSA conjugate formation. In FTIR of BSA-IONPs, transmittance was increased in amide A and B bands while decreased in amide I and II bands. In summary, native PAGE, HPLC, and FTIR analysis displayed a differential behaviour of IONPs with native and glycated BSA. These results provided an understanding of the interaction and structural modifications of glycated and native BSA which may provide fundamental repercussions in future studies.
Keywords: Albumin; Glycation; iron oxide nanoparticles

One-pot concurrent biosynthesis of biphasic CuxO (cuprous and cupric oxide) nanoparticles using leaf extract of Eichhornia crassipes and investigation of their potent healthcare applications - Moudgil, Aliesha; Varma, Sanjana; Shinde, Manish D.; Vamkudoth, Koteswara Rao; Sarkar, Dhiman M.; Shende, Rajnigandha A.; Amalnerkar, Dinesh; Chaudhari, Bhushan P. (Emergent Materials, 2022)
Eichhornia crassipes, an aquatic weed, has been used for the one-pot quick synthesis of cuprous and cupric oxide nanoparticles in this report. The identification and validation of the formed nanoparticles were successfully done by sophisticated characterization techniques such as UV–visible spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Their biomedical interventions were assessed by their antioxidant and anticancer activities. The synthesized nanoparticles have a spherical morphology with an average diameter of 10 nm. Antioxidant assay performed showed an increasing trend in a dose-dependent manner with the percentage radical scavenging activity up to 94.70% at a much higher concentration of 1000 µg/ml. The antioxidant potential at such higher concentration is suspected to invoke a change in the cytotoxic potential of the nanoparticles which is then verified by the MTT assay. A significant cytotoxic activity against HeLa (cervical cancer) and HCT 116 (colorectal carcinoma) cell lines was detected with noted IC50 values of 17.17 and 13.70 µg/ml respectively. The conclusive findings obtained are enough to substantiate the use of these nanoparticles in biomedical areas specifically in anticancer treatment due to their high toxicities. The hazards imposed by Eichhornia crassipes can be alleviated by using them as biofactories for the synthesis of a variety of nanomaterials. This helps in curbing the water pollution issues as well as the developing synthesis protocols for robust and stable nanoparticles.

Biosynthesis of gold nanoparticles by Penicillium rubens and catalytic detoxification of ochratoxin A and organic dye pollutants - Bhandari, Yogesh; Varma, Sanjana; Sawant, Amol; Beemagani, Sreelatha; Jaiswal, Neha; Chaudhari, Bhushan P.; Vamkudoth, Koteswara Rao (International Microbiology, 2023)
The environmental pollution caused by chemical dyes is a growing concern nowadays. Limitations of traditional methods opened the route for nanotechnology; owing to the versatile properties of nanomaterials, gold nanoparticles (AuNPs) became a potential strategy for different applications. In the present study, biosynthesis of gold nanoparticles (BioAuNPs) was carried out by reacting chloroauric acid (HAuCl4) with cell-free filtrate of Penicillium rubens sp. nov. NCIM 1937. The AuNPs were then characterized by UV-visible spectroscopy, HR-TEM, FTIR, and DLS analysis to further examine their efficacious biosynthesis and morphological properties including size, shape, and stability. The biogenic AuNPs are polydisperse in nature, with a mean size of 14.92 +/- 5 nm. These AuNPs exhibited promising antimicrobial activity against Escherichia coli NCIM-2065, Bacillus subtilis NCIM-2010, and Penicillium verrucosum MTCC 4935. In vitro quantitative HPLC results revealed that BioAuNPs significantly inhibited the biosynthesis of ochratoxin A (OTA). Microbial fuel cells (MFCs) are intriguing for power generation and wastewater treatment since they can directly transform chemical energy stored in organic matter to electricity by extracellular electron transfer (EET) via membrane proteins. AuNPs also showed excellent potential for dye degradation of organic pollutants, viz., methylene blue (MB), phenol red (PR), bromothymol blue (BTB), Congo red (CR), and 4-nitrophenol (4-NP). All dye removal efficiencies were estimated and fitted to pseudo-first-order processes using kinetic rate constants (Ka).The present study reveals a simple, original, and eco-friendly method for the synthesis of multifunctional biogenic AuNPs that could be effective in OTA detoxification in food products and organic pollutant removal during wastewater treatment for a sustainable environment.
Keywords: Catalytic organic dye degradation; gold nanoparticles; Ochratoxin A; Penicillium rubens; Penicillium verrucosum

Development of novel ssDNA aptamers for detection of receptor-binding domain of SARS-COV-2 - Auti, Amogh; Yadav, Pranay; Bodkhe, Rahul; Bhandari, Yogesh; Varma, Sanjana; Chaudhari, Bhushan; Rahi, Shraddha; Ghormade, Vandana; Vamkudoth, Koteswara Rao (ACS Omega, 2025)
The highly virulent and transmissible SARS-CoV-2 causes COVID-19 and poses a global public health threat. Herein cloned, expressed, and the molecular weight of the receptor-binding domain (RBD) of the SARS-CoV-2 gene encoding protein was confirmed by SDS-PAGE electrophoresis and Western blot analysis. The pivotal aim is to develop single-stranded DNA (ssDNA) aptamers for the rapid detection of SARS-COV-2 infections in humans. In this investigation, a library of nine novel ssDNA aptamers was developed by several rounds of systematic evolution of ligands by an exponential enrichment approach and assessed by an enzyme-linked aptamer assay for binding affinity against RBD antigen (Ag). An in vitro assay resulted in a varied colorimetric signal that depends on the nature of aptamer. Quantitative determination of AptRBD3, AptRBD6, and AptRBD8 aptamers exhibited excellent binding affinity against Ag in the range of 5-10 ng/mL. The putative AptRBD3, AptRBD6, and AptRBD8 aptamers were converted into peptide sequences and docked against RBD, exhibiting good binding energy of -6.8, -6.3, and -7.1 kcal/mol respectively, which were recorded. Furthermore, docking studies of ssDNA aptamers were performed using HDOCK web server to ascertain the binding mechanism and docking score perceived as -389.74, -404.28, and -390.37. Despite this, we engineered a high-affinity AptRBD3.3 aptamer that formed a single and bulged loop, which improved binding affinity, resulted in a docking score of -361.56, and exhibited sensitivity at 4 ng of Ag of SARS-CoV-2. Moreover, computational modeling of AptRBD3.3 revealed an intriguing significant binding affinity with the RBD mutant SARS-CoV-2 S-UK variant (PDB ID: 7EDG) with a docking score of -350.21. In conclusion, the AptRBD3.3 aptamer can be used for the development of lateral flow device and electrochemical sensors for rapid, low-cost, and accurate detection of COVID-19 infection in humans for point of care diagnostics.

Functionalized gold nanorods (GNRs) as a label for the detection of thyroid-stimulating hormone (TSH) through lateral flow assay (LFA) - Varma, Sanjana; Burade, Dimpal K.; Chaudhari, Bhushan P. (Emergent Materials, 2025)
Thyroid-stimulating hormone (TSH) is an important biomarker of thyroid dysfunctions. Different types of nano biosensors have been developed to detect TSH. However, there is a lacuna in the development of sensitive paper-based nano biosensors due to less sensitivity and instability of the labels. Interestingly, the intense color and localized surface plasmon resonance (LSPR) property make gold nanorods (GNRs) an efficient lateral flow assay (LFA) label instead of spherical gold nanoparticles. The rapidity, simplicity and user-friendly functioning of LFAs make them a predominant technique compared to electrochemical techniques for point-of-care diagnosis. This proof-of-concept study underlines the role of stable GNRs as a novel label for LFAs. The TSH antibody functionalized GNRs can semi-quantitatively diagnose hyperthyroidism and hypothyroidism. The limit of detection (LOD) of the LFA is 0.3 µIU/mL, determined by visually analyzing the color development at the test line without employing any quantification method. Moreover, the study provides a comprehensive understanding of seed-mediated synthesis and functionalization of GNRs, which would benefit the researchers in suitably designing the GNRs-based labels for LFAs. Considering their exceptional characteristics, GNR-based LFAs are expected to surpass other labelling nanomaterials in detecting various biological markers. This enhanced sensitivity could significantly improve the clinical utility of diagnostic kits.

Gold nanorods (GNRs): a golden nano compass to navigate breast cancer by multimodal imaging approaches - Varma, Sanjana; Bamb, Aagam Lalit; Haldar, Niladri; Gajbhiye, Virendra; Amalnerkar, Dinesh; Chaudhari, Bhushan Pradosh (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2025)
The ongoing rise in the incidences of breast cancer cases has concerned medical and scientific personnel around the world. Adequate treatment of cancer predominantly relies on the pertinent diagnosis of the type of cancer as well as other molecular and cellular details at the initial stage only. Surprisingly, up till now, there is no single, self-reliant imaging modality that helps to systematically find out the anatomical and functional events taking place inside the body. This resulted in the advent of the multimodal imaging concept, which encompasses the integration of complementary imaging modalities by designing multimodal imaging probes. Gold nanorods (GNRs) are extremely popular and effective nanoparticles for multimodal bioimaging due to their unique properties. Researchers have designed varieties of stable and biocompatible GNR-based probes for targeted and nontargeted multimodal imaging of breast cancer. However, there is a lack of investigations on the in vivo fate and the toxicity of GNRs. Thus, their preclinical to clinical translation can be attained by comprehensively determining the in vivo fate and toxicity of GNRs. The review provides details about the GNRs-based nanoprobes fabricated so far for breast cancer imaging, which, by consequent studies, can be taken up to clinical usage.
Keywords: Breast cancer; Gold nanorods; imaging probes; Multimodal Imaging

An integrated paradigm to understand the antibacterial and antifungal potential of bimetallic core-shell platinum silver (Pt@Ag) nanoparticles: A one health approach - Bamb, Aagam Lalit; Varma, Sanjana; Gade, Tejas Subhash; Palaskar, Shahaji; Vamkudoth, Koteswara Rao; Vyawahare, Niraj; Chaudhari, Pallavi M.; Chaudhari, Bhushan P. (Microbial Pathogenesis, 2025)
The concurrent occurrence of various microbial infections escalates the need to develop new treatments that can tackle multiple microbes and improve clinical outcomes. This study reports the synthesis and comprehensive evaluation of core-shell platinum-silver nanoparticles (Pt@AgNPs) designed to elucidate the antimicrobial effects while ensuring biocompatibility. The synthesis protocol was meticulously optimized to investigate the impact of precursor concentrations and reagent conditions. High-end characterization confirmed the formation of a welldefined core-shell structure with spherical morphology, crystalline nature, a face-centred cubic (FCC) lattice, high monodispersity, and stability, with a mean size of 20.344 +/- 4.492 nm. The antimicrobial potential of Pt@AgNPs was validated through a minimum inhibitory concentration (MIC) assay, revealing potent activity with MIC values of 15.6 mu g/mL for Pseudomonas aeruginosa and Staphylococcus aureus and 3.9 mu g/mL for Escherichia coli. Antibiofilm assay demonstrated significant inhibition of biofilm formation by P. aeruginosa at concentrations as low as 3.9 mu g/ml. The nanoparticles also exhibited notable antifungal activity, as indicated by an inhibition of 65.19 % for Aspergillus niger and 61.82 % for Fusarium verticillioides. Furthermore, hemocompatibility was noticed with the hemolysis assay, and the antioxidant properties of nanoparticles, assessed through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, underscored their potential to mitigate oxidative stress. This integrative study positions Pt@AgNPs as a promising platform for combating the occurrence of co-infections. The core-shell nanoparticle serves as a versatile tool in antimicrobial defence, exhibiting antibacterial, antifungal, antibiofilm, and antioxidant activity. Thus, it highlights their commercial translational potential as a next-generation antimicrobial intervention.
Keywords: Antibacterial; antibiofilm; antifungal; Antioxidant; Co-infections; Pt@Ag nanoparticles

Understanding the antimicrobial and antioxidant potential of bioinspired platinum nanoparticles synthesized using ocimum tenuiflorum - Varma, Sanjana; Bamb, Aagam Lalit; Tambe, Sayali A.; Burade, Dimpal K.; Jagdale, Swati; Pande, Bharat; Vamkudoth, Koteswara Rao; Chaudhari, Bhushan P. (BioNanoScience, 2025)
The emergence of infectious diseases has highlighted the need for novel and effective antimicrobial agents. Platinum nanoparticles (PtNPs) could act as a potent antimicrobial agent due to their unique physicochemical properties. However, the chemical or physical synthesis methods of PtNPs have drawbacks, like irregular shape and use of toxic chemicals. These drawbacks can be effectively overcome by using the biological method synthesis. Thus, this study presents the green synthesis of platinum nanoparticles (PtNPs) using Ocimum tenuiflorum leaf extract as a bio-reductant. The study also comprehensively encompasses the role of multiple process parameters for the green synthesis of PtNPs. The high-resolution transmission electron microscopy (HR-TEM) revealed spherical PtNPs with an average size of 2.36 ± 0.5 nm that exhibits excellent stability (zeta potential, −45.67 ± 2.57 mV). Phytochemical analysis of aqueous O. tenuiflorum leaf extract was performed to assess the bioactive compounds like saponins, phenols, and tannins, reducing sugars and flavonoids. The PtNPs demonstrated significant antioxidant activity of 86.9 ± 0.12% at 10 µg/mL. Further, the biosynthesized PtNPs showed efficient antimicrobial activity with a minimum inhibitory concentration (MIC) of 6.25 µg/mL against Escherichia coli and 1.5 µg/mL against Staphylococcus aureus. These findings highlight the therapeutic potential of eco-friendly PtNPs for pharmaceutical and biotechnological applications.